Literature Review: Kajian Potensi Energi Surya Alternatif Energi Listrik - Kharisma, Amrul; Pinandita, Satria; Jayanti, Ari Endang (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2024)
The demand for electrical energy is increasing every year and coal is also predicted to run out in the next few decades, so it must be replaced with new renewable energy such as solar energy sourced from solar radiation. This research aims to find out the potential of solar energy as an alternative source of electrical energy that can replace coal. This research is a type of qualitative research with a literature review method. Research data was collected from secondary sources from journals with the same research focus in 2019-2024 and the national energy balance analysis report (National Energy Council. The findings of the study show that national energy management has been regulated by the National Energy Council in the National Energy Policy (KEN) guidelines. Solar energy is encouraged by the government to be developed in Indonesia because of its huge potential considering that Indonesia is at the equator and has a tropical climate so that the intensity of solar radiation tends to be constant and comprehensive throughout Indonesia. The supply of solar energy from 2018-2022 continues to increase, this also encourages the development of solar power plants in Indonesia. In addition, the use of solar energy as a raw material for solar power plants also encourages battery investment, because sunlight has intermittent properties so that temporary storage such as batteries is needed to store energy before being converted into electrical energy. Thus, solar energy has a great opportunity to be developed in Indonesia considering the potential geographical location of the country and as a way to attract investors.